The effects of accounting information systems on organisational performance among conventional commercial banks in Jordan
Organisational performance is the ontological benchmark to any organisation in terms of vision and mission achievements. In order to ensure that the bank is staying competitive, then the organizational performance plays a significant role to ensure that the organisation could be successful in the future. Hence, the purpose of this study is to investigate the effects of the accounting information systems (AIS) qualities in terms of services, systems, and data, as a success factor on organisational performance proxy of the banking sector. The study further tests the moderating effects of organizational culture on the model. Based on literature review, we include four predictors or determinants for the organisational performance namely, information quality, service quality, system quality and data quality. Data is collected using questionnaire survey approach on employees of the selected commercial banks in Jordan. A total of 520 questionnaires are distributed and 273 sets are considered for the analysis, or about 53 per cent response rate. Partial least squares structural equation modelling (PLS-SEM) has been employed as a research methodology using a software, Smart PLS version 3.2. The hypotheses of the final model results suggest that the information quality, service quality, system quality are the significant determinants or factors of organisational performance, meanwhile the results indicated that data quality has no relationship with organizational performance. Further analysis reveals that organisational culture moderate significantly and positively to the model on relationship between AIS success factors (information quality, service quality, system quality) and organisational performance, while the results have shown the OC has not moderate significantly and positively the relationship between data quality and the organizational performance. Suggesting that the adoption of positive culture by the banks on AIS will improve their performance. Therefore, effective accounting information systems in well-managed organisational culture environment can improve work performance and increase the efficiency of the operational activities both in the short-run and long-run. The results from this research contributes a holistic framework for measuring organisational performance based AIS qualities. The finding triggers future researchers to conduct similar studies for other sectors in Jordan, possibly in different contexts and perspectives.